A single man [videorecording (DVD)] - Firth, Colin, 1960-; Moore, Julianne; Hoult, Nicholas, 1989-; Goode, Matthew, 1978-; Goodwin, Ginnifer; Hamm, Jon, 1971- (Lionsgate, 2021)
Based on the novel of the same name by Christopher Isherwood. Set in Los Angeles in 1962 at the height of the Cuban missile crisis, it is the story of a British college professor who is struggling to find meaning in his life after the death of his longtime partner. The story is a romantic tale of love interrupted, the isolation that is an inherent part of the human condition, and, ultimately, the importance of the seemingly smaller moments in life.